Relationship Analysis of Soil Bulk Density, Available K, and Slope to Productivity of Salak Pondoh at Padang Jaya, North Bengkulu - Muhammad Yakub; M. Faiz Barchia; Usman K.J. Suharjo (TERRA : Journal of Land Restoration, 2020)
Salak (Zalacca edulis Gaertn. Voss) is one of the most populair native fruits of Indonesia, consumed as a table fruit by most Indonesians. However, the yield of salak pondoh grown in Bengkulu is still lower than that in their native soil Java, believed to have more suitable soil properties for growing salak pondoh. The objective of this research were to evaluate the relationship of soil bulk density, available K, and slope to the productivity of salak pondoh grown at Padang Jaya Regency, North Bengkulu. We did a survey to collect data on soil bulk density (BD), available K (K), and slope as well as the productivity of salak pondoh grown at Padang Jaya from November 2017 to May 2017. The results showed that there was a significant relationship between soil characteristics and salak productivity, as shown in a linear model of Y = 2.929 -1.070 BD + 0.069 K - 0.126 Slope. Soil K was positively correlated to salak productivity, suggesting that salak productivity increased with an increase in soil K.  On the other than, soil bulk density and slope were negatively correlelated to salak productivity, indicating that salak productity decreased with an increase in slope and in soil bulk density.